TGF-β signaling pathway in early mouse development and embryonic stem cells. (28th November 2017) - Liu, Chang; Peng, Guangdun; Jing, Naihe
Abstract: TGF-β superfamily signaling pathways essentially contribute to the broad spectrum of early developmental events including embryonic patterning, cell fate determination and dynamic movements. In this review, we first introduced some key developmental processes that require TGF-β signaling to show the fundamental importance of these pathways. Then we discuss how their activities are regulated, and new findings about how the TGF-β superfamily ligands bind to the chromatin to regulate transcription during embryo development.